2016
DOI: 10.1186/s12917-016-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin free of lipopolysaccharide can induce a proinflammatory response of macrophages

Abstract: BackgroundLactoferrin (LF) is an 80 kDa glycoprotein which is known for its effects against bacteria, viruses and other pathogens. It also has a high potential in nutrition therapy and welfare of people and a variety of animals, including piglets. The ability to bind lipopolysaccharide (LPS) is one of the described anti-inflammatory mechanisms of LF. Previous studies suggested that cells can be stimulated even by LPS-free LF. Therefore, the aim of our study was to bring additional information about this possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…LF induced potent antibacterial activity in MDSCs, which could be exploited in future therapeutic applications. Activation of NF-κB transcription factor is a known downstream target of LF (36,37). We confirmed upregulation of NF-κB in neonate myeloid cells by LF and demonstrated that selective inhibition of NF-κB abrogated the effect of LF.…”
Section: Methodssupporting
confidence: 63%
“…LF induced potent antibacterial activity in MDSCs, which could be exploited in future therapeutic applications. Activation of NF-κB transcription factor is a known downstream target of LF (36,37). We confirmed upregulation of NF-κB in neonate myeloid cells by LF and demonstrated that selective inhibition of NF-κB abrogated the effect of LF.…”
Section: Methodssupporting
confidence: 63%
“…It is therefore likely that LTF also plays an indirect role through other “sensing” receptors, such as the receptor for advanced glycation end products (RAGE) and the myeloid cell triggering receptor TREM-1. These are less prominent, but stimulation through these receptors also triggers NF-κB activation and subsequent transcription of genes for inflammatory cytokines and chemokines ( 60 , 61 ). This includes expression of IL-1α and β, IL-6, IL-8, TNF-α, IL-12, IL-15, IFN-α, and IFN-β, cyclooxygenases (COX1 and COX2), and inducible nitric oxide (nitric oxide) synthase; they also include the gene products important for initiation of adaptive immune responses (such as CD80, CD86, and CD40) ( 62 ).…”
Section: Inflammation: An Immune Response To Injurymentioning
confidence: 99%
“…This includes expression of IL-1α and β, IL-6, IL-8, TNF-α, IL-12, IL-15, IFN-α, and IFN-β, cyclooxygenases (COX1 and COX2), and inducible nitric oxide (nitric oxide) synthase; they also include the gene products important for initiation of adaptive immune responses (such as CD80, CD86, and CD40) ( 62 ). These diverse mediators initiate a cascade of specific and non-specific responses including bone marrow stimulation for the production of monocyte and neutrophil precursors (Figure 1 ) ( 61 ). Finally, it should be mentioned that LTF can also activate complement, through the classical pathway, which assists in mediating attraction of innate cells to inflammatory sites ( 63 ).…”
Section: Inflammation: An Immune Response To Injurymentioning
confidence: 99%
“…These results are consistent with our previous JEV study showing that bLF inhibits dengue virus infection mainly at the steps of virus attachment [ 6 ]. Also, bLF added after viral attachment inhibited DENV-2, and that might associate with the multiple enzymatic activities of internalized lactoferrin, especially RNase, [ 25 ] or with innate immunity triggered by bLF through a Toll-like receptor [ 26 ].…”
Section: Discussionmentioning
confidence: 99%